Economics of Buffalo Milk Production – A Case Study of Composite Andhra Pradesh - Vijayudu, Gudipati (Journal of Rural Development, 2015)
Milk production is a complex process involving a number of genetic and nongenetic factors. Variation in genetic potential, feeding and management practices influence the yield of milk for cattle and buffaloes. Costs and Returns of dairying are important concerns of dairy farmers. The results of the study presented in the paper examine the economics of buffalo milk production and productivity in three villages of different levels of agricultural development in Composite Andhra Pradesh. The districts covered from the three regions are: Guntur, Nalgonda and Kurnool. Analysis presented is in respect of three breeds of buffaloes – murrah breed, graded murrah breed, and non-descriptive/desi, and five categories of dairy households - agricultural labour, marginal, small, semi-medium and medium farmers. The results flowing from the Input-Output Analysis, Cobb-Douglas Production Function, X2 test, and Cost-benefit Ratio are presented district-wise and buffalo category-wise. Emphasis is on intensification of the drive for cross breeding of species, as graded murrah is considered highly remunerative in terms of yield of milk and adoption of scientific management practices.